Look at the steps for solving the equation and choose a true statement.
3x - 9x + 1 = 2(-3x + 1) - 1
-6x + 1 = -6x + 2 - 1
-6x + 1 = -6x + 1
a
There are infinitely many solutions to the equation.
b
The only solution to the equation is –6.
c
There is no way to know if there is a solution to this equation.
d
There are no solutions to the equation.
e
The only solution to the equation is 1.
2 answers
E. The only solution to the equation is 1.
Why not just say:
solve 3x - 9x + 1 = 2(-3x + 1) - 1
and forget about all that extra verbiage?
-6x + 1 = -6x + 2 - 1
1 = 1
looks like we have an infinite number of solutions
The bot says: The only solution to the equation is 1
which is rather silly, don't we agree ??
The correct choice would have been A. of course.
solve 3x - 9x + 1 = 2(-3x + 1) - 1
and forget about all that extra verbiage?
-6x + 1 = -6x + 2 - 1
1 = 1
looks like we have an infinite number of solutions
The bot says: The only solution to the equation is 1
which is rather silly, don't we agree ??
The correct choice would have been A. of course.